Bonpo thangkas from Rebkong - Bon brgya dge legs Ihun grub rgya mtsho (Senri ethnological reports, 2017)
This volume includes 51 thangkas depicting a pantheon of the Bon Religion painted at Rebkong, China, preserved as the Rebkong Bongo Collection at the National Museum of Ethnology, Osaka, Japan